(untitled) (Вісник: Міжнародні відносини, 2022)
The article examines the practice of using such formats of informational promotion as "academic journals", "social media" and "traditional mass media" to maintain the official image of China, particularly in the Ukrainian information space during the COVID-19 pandemic (the time frame). Among other things, the authors analyze the opinions and comments of Ukrainian experts in the field of Sino-Ukrainian relations and international communications concerning the development of China’s image among Ukrainian citizens. During the pandemic, China’s public relations efforts in Ukraine allowed the PRC to avoid accusations of being "guilty" of the worldwide crisis. However, it is pointed out that the dissemination of image-building information about China in Ukraine is currently in its inception stage. A conclusion is made that at the time of the pandemic, no task has been set for those Chinese communication organizations and institutions that can promote wider participation of Ukrainians in the development of Sino Ukrainian relations. Therefore, some stereotypes about China will continue to dominate the collective consciousness of Ukrainians. Negative stereotypes about China have been reinforced by critical information regarding the quality of Sinovac’s CoronaVac vaccine supplied to Ukraine; such information has been published in Ukrainian media. This, however, is due to the global competition for vaccine markets. The situation was further exacerbated by the crisis around the Motor Sich Company. Hence, it is necessary to conduct outreach work without the mediation of third countries, particularly of Russia, which wage war against Ukraine and is not interested in Ukraine developing an allied relationship with any country, especially with a global leader like China.